The study on Chinese temples in Melaka / Ng Lee Lee - Ng , Lee Lee (1984)
The study of Chinese temples helps us to examine in greater detail on the various aspects of the Chinese religion culture, belief and practises . This exercise seeks to explore, specifically, on the sociological aspects of the Chinese temples, which play a very important role in the lives of the Chinese community. Chapter 2 aims to describe on the aspects of temples and the theology of Chinese religion upon which the practises, beliefs and culture is based. With this knowledge, it is hoped that we can throw some light on the reasons why such celebrations or activities take place and on the structure and social organization of the temples. Chapter 3 will give a detailed description of the Chinese temples in Melaka on which this research is being conducted. This includes aspects, such as characteristics, ditribution, development and future plans of the temples. Chapter 4 on the other hand aims to discuss on the types of celebrations and activities of the temples whereby in the course of describing how these celebrations take place, we will touch upon the significance of such celebrations, activities and ceremonies based on the theology of Chinese religion. Chapter 5 seeks to discuss on the social organization of the temples. In conclusion, we discuss on the continuity of the Chinese temples in the midst of the social changes in society.